Trade liberalization, profitability, and financial leverage - Baggs, Jen; Brander, James A (Journal of International Business Studies, 2006)
We investigate the effects of trade liberalization on profitability and financial leverage using Canadian data arising from implementation of the Canada–US Free Trade Agreement. We find that falling domestic tariffs are associated with declining profits, especially for import-competing firms, while falling foreign tariffs are associated with increasing profits, especially for export-oriented firms. Also, import tariff reductions tend to increase leverage while export tariff reductions tend to decrease leverage.